2001
DOI: 10.1159/000059387
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Cytokines: Expression and Action in the Brain

Abstract: Transforming growth factor-β1 (TGF-β1) and interleukin (IL)-10 gene expression is equivocal in normal brain and upregulated in over a dozen central and peripheral diseases/disorders. The patterns of specific expression of cytokines differ in these diseases. Published data indicate that these cytokines are produced by and act on both neurons and glial cells. Although their actions are commonly viewed as ‘anti-inflammatory’, they protect neurons and downregulate the responses of glial cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(65 citation statements)
references
References 148 publications
(223 reference statements)
1
64
0
Order By: Relevance
“…[110] In the TGF-β superfamily, only TGF-β1, produced by activated microglia, and TGF-β2, produced by astrocytes and neurons. [111] TGF-β1 and TGF-β2 increased prominently after ischemic stroke. After Ischemic stroke, TGF-β produced by activated M2 phenotype macrophage, plays an anti-inflammatory role and contributes to recovery after brain injury.…”
Section: Il-1βmentioning
confidence: 88%
“…[110] In the TGF-β superfamily, only TGF-β1, produced by activated microglia, and TGF-β2, produced by astrocytes and neurons. [111] TGF-β1 and TGF-β2 increased prominently after ischemic stroke. After Ischemic stroke, TGF-β produced by activated M2 phenotype macrophage, plays an anti-inflammatory role and contributes to recovery after brain injury.…”
Section: Il-1βmentioning
confidence: 88%
“…Furthermore, the CNS was thought to lack of conventional lymphatic drainage. It was reported that a number of anti-inflammatory substances such as TGF-, Fas ligand and ganglioside, which inactivate or kill immune cells (Becher et al, 1998;Benveniste, 1998;Irani, 1998;Bechmann et al, 1999;Gozes et al, 1999;Pender and Rist, 2001;Vitkovic et al, 2001). Increasing reports, however, demonstrate that some degree of immune surveillance of the CNS exists and is crucial to prevent disease development.…”
Section: Unique Immune Properties Of the Central Nervous Systemmentioning
confidence: 99%
“…Given the ability of AS101 to protect nigrostriatal dopaminergic neurons in animal models of PD, namely by neurotrophic, anti-apoptotic and anti-inflammatory mechanisms, it was proposed as a promising agent to treat PD (Sredni et al, 2007). Since the effect of IL-10/AS101 does not seem to be cell type-specifically regulated, it may explain the deprivation of neurotrophic factors in several CNS diseases where elevated expression of IL-10 is described (Vitkovic et al, 2001), although the levels of pro-inflammatory agents are usually increased in those diseases. The principal function of IL-10 appears to be limitation and ultimately termination of inflammatory responses (Moore et al, 2001).…”
Section: Negative Regulation Of Gdnf Expressionmentioning
confidence: 99%